Sistem Informasi Pengajuan Judul Skripsi Berbasis Online Di Fakultas Ilmu Sosial - Irvan Cianstury, Asnawati, Feri hari Utami (Jurnal Ilmiah Binary STMIK Bina Nusantara Jaya Lubuklinggau, 2023)
The development of science and technology along with the times can support all processes and activities carried out by humans. A computer is a sophisticated tool or electronic object that is broadly composed of hardware and software that work together in processing data entered or provided by the user. Computers have many advantages, they can process data such as the form of numbers, letters, sounds, symbols, and others. With computer technology, data processing will be easier and more efficient so the users do not take a long time to manage data. The Communication sciences Program Studies, Faculty of Social Sciences, University of Dehasen Bengkulu, is still not effective and efficient in terms of campus services, especially for students who want to submit final assignments, especially when submitting thesis titles because they are still using the manual method. By the study program, the files are recaptured one by one into Microsoft Excel, so there is a very high risk of data input errors due to human error, not to mention the possibility of duplicate titles that may occur, where titles that have been submitted can be submitted again by other students. This process needs to be supported by the implementation of technology, for example the use of the web as an implementing medium. The author uses the PHP programming language and MYSQL database which aims to build an information system for submitting a thesis title which is expected to support and facilitate the process of submitting a thesis title and easily obtain information about campus services, especially when submitting a thesis at the University of Dehasen Bengkulu..